A revealed damage cost method to evaluate environmental performance of production: Evaluating treatment efficiency of emissions and scaling treatment cost bounds. (1st September 2018) - Chen, Shuzhen; Wu, Desheng
Abstract: Environmental performance indices are in great demand for environmental policy support. This paper addresses the particular problem of evaluating environmental performance of industries and identifying the worst performed industries that should be strictly regulated. Specifically, an input-output analysis method is developed to disentangle the environmental pressures of production processes; treatment costs are introduced to reveal the damage costs of relevant pressures which is integrated in the DEA based index to restrict the weight assignment. The proposed method is advantageous in data requirements as well as definition of process boundaries and can alleviate the underestimation of damages from predominant pressures. The results of evaluation provide a more reliable reference to industrial regulation.